CLIMATE-SMARTAGRICULTUREAND ITS MANAGEMENT - Mahesh Singh, Meenakshi Sharma (International Journal of Modern Agriculture, 2021)
With the increase in the population size, the need for their feed is also increasing. Agriculture play a major role in providing food across the world. Agricultural industries are the largest industries to be known and also help in the economic development of a nation. Agricultural industry face a major challenge related with the global climatic variations.Farmers from all over world face serious problems with changeable weather patterns, smaller growing duration, drought, extreme temperature, amplifiedintroduction to pest and crop diseases. Climate-smart practice will help farmers to adapt and prepare for impacts of climatic variations. The major aim behind climate-smart agriculture is to improve agricultural productivity, making farm more compatible against the climatic variations, and decreasing greenhouse gas emission from the agricultural goods. As climate-smart agriculture techniques comes up with some challenges like- lack of knowledge about it, lack of resources, socio-economic constrains at farm level etc. To overcome all these challenges, government authorities, institutions and major stakeholders should contribute in climate-smart agriculture by proving various educational programs, by helping financially, and also by providing tools. Equipment’s should be provided that will help farmers for timely detection of climatic variations and on the basis of that they can opt the suitable crop. In future it can be used to send signals to the farmers after detecting the amount of water required for any crop development.